A review of the fate of engineered nanomaterials in municipal solid waste streams. (May 2018) - Part, Florian; Berge, Nicole; Baran, Paweł; Stringfellow, Anne; Sun, Wenjie; Bartelt-Hunt, Shannon; Mitrano, Denise; Li, Liang; Hennebert, Pierre; Quicker, Peter; Bolyard, Stephanie C.; Huber-Humer, Marion
Highlights: Literature associated with ENM-containing waste was reviewed and summarized. Knowledge gaps about ENM release during waste treatment exist. Key processes and mechanisms of ENM fate and transport were reviewed. Specific research questions have been identified. Abstract: Significant knowledge and data gaps associated with the fate of product-embedded engineered nanomaterials (ENMs) in waste management processes exist that limit our current ability to develop appropriate end-of-life management strategies. This review paper was developed as part of the activities of the IWWG ENMs in Waste Task Group. The specific objectives of this review paper are to assess the current knowledge associated with the fate of ENMs in commonly used waste management processes, including key processes and mechanisms associated with ENM fate and transport in each waste management process, and to use that information to identify the data gaps and research needs in this area. Literature associated with the fate of ENMs in wastes was reviewed and summarized. Overall, results from this literature review indicate a need for continued research in this area. No work has been conducted to quantify ENMs present in discarded materials and an understanding of ENM release from consumer products under conditions representative of those found in relevant waste management process is needed. Results also indicate that significant knowledge gaps associated with ENM behaviour exist for each waste management process investigated. There is a need for additional research investigating the fate of different types of ENMs at larger concentration ranges with different surface chemistries. Understanding how changes in treatment process operation may influence ENM fate is also needed. A series of specific research questions associated with the fate of ENMs during the management of ENM-containing wastes have been identified and used to direct future research in this area.